Prospects of microwave processing: An overview - Das, S.; Mukhopadhyay, A. K.; Datta, S.; Basu, D. (Bulletin of materials science, 2009)
Microwave processing has been emerging as an innovative sintering method for many traditional ceramics, advanced ceramics, specialty ceramics and ceramic composites as well as polymer and polymer composites. Development of functionally gradient materials: joining; melting; fibre drawing; reaction synthesis of ceramics; synthesis of ceramic powder, phosphor materials, whiskers, microtubes and nanotubes; sintering of zinc oxide varistors; glazing of coating surface and coating development have been performed using microwave heating. In addition, microwave energy is being explored for the sintering of metal powders also. Ceramic and metal nanopowders have been sintered in microwave. Furthermore, initiatives have been taken to process the amorphous materials (e.g. glass) by microwave heating. Besides this, attempt has been made to study the heating behaviour of materials in the electric and magnetic fields at microwave frequencies. The research is now focused on the use of microwave processing for industrial applications.